A comparison of hip joint kinetics during the barbell hip thrust, deadlift and back squat - Bezodis, I.; Needham, L.; Brazil, A. (ISBS Proceedings Archive (Michigan), 2018)
The barbell hip thrust, deadlift and back squat are all exercises designed to strengthen the hip extensor muscles. The aim of this study was to directly compare hip joint kinetics in the lifting phase of the barbell hip thrust with those in the deadlift and back squat. Six resistance-trained men performed one set of three repetitions at 90% 1RM of each exercise. Kinematic (250 Hz) and kinetic data (1000 Hz) were used to calculate hip angle and moment throughout each lifting phase. Analysis of continuous data revealed that the hip extensor moment was significantly greater early in the lifting phase in the deadlift and later in the lifting phase in the hip thrust. All three exercises clearly facilitate the strengthening of the hip extensors, and careful consideration of the specific desired adaptation is recommended when selecting exercises for this purpose.